PENERAPAN SERTIFIKASI HALAL UNTUK MAKANAN RUMAHAN DI ROKAN HULU RIAU - Rosadi, Syukri; Andrini, Rozi; Resti, Okfi (STAI Asy-Syukriyyah, 2023)
The purpose of this research is to describe how important the awareness of entrepreneurs is about the halal insurance system in the domestic food industry. that domestic foods with halal certification and containing halal brands offer positive values ​​that can expand the market, increase turnover, flexibility and business development in Rokan Hulu Riau. This research is a qualitative study with descriptive data collection techniques using observation, interviews and documentation techniques. Researchers use data reduction, data collection, presentation, and inference to analyze data. The results of this study show that the importance of entrepreneurs' awareness of halal assurance system of the domestic food industry, awareness of halal certification significantly affects consumers' purchase interest in Rokan Hulu Riau. The Halal label provides clearer information about the product and successfully improves the quality of the product. Halal-certified Rokan Hulu Regency home food store operators experience a positive effect: first, they can more easily market their products without suspicion. Second, it can convince buyers or consumers that the products produced and sold are halal products and are suitable for consumption even for a long time. Third, continuous turnover growth, which can support entrepreneurship and business development.